Reflexões sobre a graduação: trajetória pessoal no curso de Medicina da UFSCAR - Ramos, Emerson Pereira (Universidade Federal de São Carlos, 2021)
The completion of course work is an instrument that, through narrative and theoretical background, allows the student to describe the medical course at the Federal University of São Carlos. This synthesis can be performed by adding records from the reflective portfolio, covering dimensions of teaching, assistance and research. This work was done with the objective of describe my trajectory in the Medical course at the Federal University of São Carlos. This description will be made through reflective narratives supported by theoretical references. The introduction consists in describing my path taken since the beginning of the Medical course, going through the educational units and detailing other practical activities performed, describing the most important points and their relevance to my medical formation
Reflections on graduation: personal trajectory in the medical course of UFSCAR
Keywords: Ensino de graduação em Medicina; Educação médica; Saúde ocupacional; PBL; Medical education; Occupational health; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM